Parental involvement experienced by adolescent college students living away from home - Erpe, Jesu Francesca S.; Jamero, Josephine Louise F.; Padua, Christian Joseph A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
This qualitative study aimed to discuss the experiences of parental involvement provided by the parent and experienced by the adolescent college student during their stay throughout college while living away from home. Fifteen parent-student dyads were given online questionnaires and were interviewed. From their responses, emergent themes were identified and thematic analysis was used for discussion. The results show that the experiences of parental involvement that were provided and received were similar to both the parent and the adolescent college student, respectively. These experiences were classified under the categories of financial, academic, social, emotional, health, safety, extracurricular, and principles and beliefs. While there was a general consistency with their accounts of experience, there were notable discrepancies as well. Parents placed more importance on principles and religious beliefs than that with their children. There was also a disparity in the perception of openness of communication from the parents with that of the students accounts as the student became more selective with their sharing over the years. Students also became proactive when the parents lacked involvement especially in the area of finances.
submitted
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman
Keywords: Parent and teenager -- Philippines; Parent and child -- Philippines